PENGARUH TEKANAN INJEKSI BAHAN BAKAR TERHADAP TEMPERATUR GAS BUANG AUXILIARY ENGINE NO. 1 DI MT. KAKAP - Nugraheni, Salsabila; Edy Kristiyono, Antonius; Yudha Yudianto, Prima; Retno Gunarti, Monika; Marlia Sandi, Wulan (Penerbit Lafadz Jaya, 2026)
Auxiliary engines in marine diesel generators frequently experience exhaust gas temperature (EGT) deviations due to suboptimal fuel injection pressure, contributing to inefficient combustion and increased emissions amid IMO 2025 sulfur regulations. This study aims to analyze the effect of fuel injection pressure on EGT in Auxiliary Engine No. 1 (Yanmar 6NY16L) onboard MT. Kakap and identify causal factors. Employing a sequential exploratory mixed-methods design, the population comprised all six cylinders with purposive sampling on the problematic cylinder (deviation >40°C) and 50 data points from pre-post maintenance measurements in April 2025. Instruments included injection pressure testers, EGT pyrometers, logbooks, and semi-structured interviews, analyzed via thematic coding, paired t-test, and Pearson correlation. Results revealed significant pressure increase from 200 to 240 kgf/cm² post-maintenance, normalizing EGT to 260°C average (t=9.834, p=0.01) with strong positive correlation (r=0.952). In conclusion, routine injector maintenance at 1500-2000 running hours prevents EGT deviations and enhances operational efficiency.